What ever happened to modernism? - Josipovici, Gabriel, 1940- (Yale University Press, 2010)
The quality of today's literary writing arouses the strongest opinions. For novelist and critic Gabriel Josipovici, the contemporary novel in English is profoundly disappointing--a poor relation of its groundbreaking Modernist forebears. This agile and passionate book asks why. Modernism, Josipovici suggests, is only superficially a reaction to industrialization of a revolution in diction and form; essentially, it is art arriving at a consciousness of its own limits and responsibilities. And its origins are to be sought not in 1850 or even 1800, but in the early 1500s, with the crisis of society and perception that also led to the rise of Protestantism. With sophistication and persuasiveness, Josipovici charts some of Modernism's key stages, from Dürer, Rabelais, and Cervantes to the present, bringing together a rich array of artists, musicians, and writers both familiar and unexpected--including Beckett, Borges, Friedrich, Cézanne, Stevens, Robbe-Grillet, Beethoven, and Wordsworth. He concludes with a stinging attack on the current literary scene in Britain and America, which raises questions not only about national taste, but about contemporary culture itself. Gabriel Josipovici has spent a lifetime writing and writing about other writers. This book is a strident call to arms and a tour de force of literary, artistic, and philosophical explication that will stimulate anyone interested in art in the twentieth century and today.